Differential Involvement of the P2Y1 and P2YT Receptors in the Morphological Changes of Platelet Aggregation - Eckly, Anita; Gendrault, Jean-Louis; Hechler, Béatrice; Cazenave, Jean-Pierre; Gachet, Christian (Thrombosis and Haemostasis, 2001)
The relative contributions of the P2Y1 and P2YT receptors to the morphological changes induced in platelets by ADP or ADP-releasing agonists were assessed using two P2 antagonists, A2P5P and ARC67085, selective for P2Y1 and P2YT, respectively. The P2Y1 receptor was found to be involved in i) the centralization of secretory granules elicited by ADP, ii) the formation of filopodia induced by released ADP in weakly activated platelets and iii) actin polymerization and the cyto-skeletal translocation of cdc42, rac1 and rhoA, in an integrin IIb3 dependent manner, in ADP-stimulated platelets. In contrast, the P2YT receptor was shown i) to be essential for the formation of stable macro-aggregates, ii) to enhance actin polymerization and the cytoskeletal translocation of small GTPases, probably through amplification of platelet aggregation, and iii) not to be involved in the early steps of platelet activation since its blockade did not affect the cytoskeletal translocation of rhoA.
Keywords: ADP receptors; platelet aggregation; morphology; cytoskeleton; GTPases